FACTORS INFLUENCING MATERNAL LABOR COMPLICATION IN KUTAI KARTANEGARA REGION - Widya Astutik; Djaswadi Dasuki; Herlin Fitriani Kurniawati (Belitung Nursing Journal, 2018)
Background: To decrease maternal mortality rate until 70 per 100,000 living birth in 2030 (SDG’s) has become the health priority. In fact, the maternal mortality rate in Indonesia is still very high, and almost two-third maternal mortality is caused by maternal labor complications. Objective: The objective of the study was to investigate the factors influencing maternal labor complications in Kutai Kartanegara Region Indonesia in 2017. Methods: This was a correlational study with cross sectional design. The populations in the study were women who had labor process in the area of Kutai Kartanegara Region. There were 95 respondents selected using purposive sampling. Data were collected using questionnaires and medical records. Chi-square and logistic regression were used for data analysis. Results: Most of the respondents had maternal labor complication (53.7%). The highest complication occurred was prolonged labor (58.9%). Factors influencing maternal labor complication were antenatal care, mother’s age, education level, parity, and distance of pregnancy. Age was identified as the most dominant variable influencing maternal complication, with the value of OR was 5.837, which indicated that high-risk-age mothers have 5.837 times of labor complication than mothers with no risk age. Conclusion: Antenatal care, age, education, parity and distance of pregnancy had correlation with maternal labor complications, and its most dominant variable was age.